Nebulised beclomethasone dipropionate in recurrent obstructive episodes after acute bronchiolitis. Issue 12 (December 1988) - Carlsen, K H; Leegaard, J; Larsen, S; Orstavik, I
Abstract : Forty four children with recurrent obstructive episodes after acute bronchiolitis in infancy were treated with nebulised beclomethasone dipropionate or placebo for eight weeks in a randomised double-blind study. They were seen monthly for a year afterwards, and also if they had acute respiratory illnesses with or without bronchopulmonary obstruction. The two treatment groups were well matched. The children receiving active treatment had significantly fewer symptomatic respiratory illnesses and fewer episodes of bronchopulmonary obstruction during the follow up period. The children given placebo had significantly higher obstructive scores during the study period, and they were treated with inhaled beta 2 agonists and theophylline for longer periods of time during the follow up period. The results suggest that nebulised beclomethasone dipropionate may have prolonged effects on subsequent asthmatic symptoms after termination of treatment in children with recurrent obstructive episodes after acute bronchiolitis.